Perlindungan Korban Kejahatan dalam Perspektif Viktimologi dan Sistem Peradilan Pidana - Sumardiono , Muslim; Sugianto, Sugiato (FOCUS, 2026)
Victims of crime are parties who directly suffer harm as a result of criminal acts, including physical, psychological, economic, and social losses. However, in practice, the criminal justice system tends to marginalize victims because law enforcement remains predominantly offender-oriented. As a result, victims are often positioned merely as witnesses and do not receive adequate fulfillment of their rights. This study aims to examine the concept of victim protection from a victimological perspective and to analyze the legal position and role of crime victims within the criminal justice system. This research employs a normative juridical method using statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials. The findings indicate that victimology recognizes victims as legal subjects entitled to protection, recognition, and recovery for the harm they have suffered. Victim protection extends beyond legal safeguards to include physical and psychological protection, prevention of secondary victimization, and recovery through restitution and compensation mechanisms. Nevertheless, the role of victims within the criminal justice process remains relatively weak. Therefore, strengthening regulatory frameworks and shifting law enforcement paradigms toward a more victim-oriented approach are necessary to achieve a fair and humane criminal justice system.